(untitled) (Faridpur Medical College Journal, 2017)
Hemangioma is one of the most common benign tumors of infancy and occurs in approximately 5-10% of infants. The treatment options for problematic haemangioma are intralesional and systemic steroids, chemotherapeutic agents including vincristine and interferon-alpha, laser therapy or surgical intervention. In this case series effectiveness of propranolon was observed on haemangioma. This study was conducted in the Department of Pediatric Surgery, Faridpur Medical College Hospital, Faridpur and Shahid Ziaur Rahman Medical College, Bogra. This study period was from January 2013 to December 2015. A total of 38 patients of haemangioma were admitted in Pediatric Surgery ward in FMCH and 26 patients in SZRMCH. These 54 patients were counseled about the study in detail. First dose of propranolol was given at a dose of 3 mg/kg/day in three divided doses. Pulse and blood pressure were recorded during initial 3 hours. Patients were then advised to continue with this treatment at home, with monthly follow-up. Total number of patients were 54. Of them 11 were male and 43 were female, giving a male: female ratio of 1:4. 60 % of the patients (32) were in <6 months. After 1 month, sign of regression was marked in all cases. Complete regression was seen in 6 patients (11.1 %) during second follow-up after 3 months of treatment. Only 4 patient required 9 months to reach the complete recovery. This case series contributes to the growing evidence that oral propranolol is efficacious and safe, with a careful dosing and monitoring. We hope a national guidelines will be developed in time for use of propranolol to treat the haemangioma. Faridpur Med. Coll. J. Jul 2017;12(2): 71-74